Unusual occurrence of tuberculosis in mature cystic teratoma (Nepal Journal of Obstetrics and Gynaecology, 2022)
Mature cystic teratoma is a common benign germ cell tumor of ovary. Unusual presentation can be seen in mature cystic teratoma like struma ovarii, carcinoid tumor, and malignant transformation. Detection of tuberculosis in mature cystic teratoma is uncommon. Here, a 57-years-female who presented with abdominal mass and pain abdomen who had tuberculosis in mature cystic teratoma